UPAYA PENINGKATAN AKTIVITAS BELAJAR MELALUI MODEL GROUP INVESTIGATION MATA PELAJARAN BAHASA INDONESIA KELAS VII-7 SMPN 1 NAMORAMBE - Erni Lamria Simamora (Universitas Negeri Medan, 2016)
Abstrak : Learning Activities Improvement Efforts Through The Implementation Of Type Cooperative Learning Group Investigation Subject In Indonesian Class VII-7 SMPN 1 Namorambe. This research implement cooperative learning model type group investigation. With the research subjects were students of class VII-7 SMP Negeri 1 Namorambe, totaling 33 students. The results of the research; (a) the student activity observed first cycle of writing and reading (45%), work (24%), ask peers (11%), ask the teacher (7%), and are not relevant to KBM (14%). Activities observations Cycle II students writing and reading (26%), work (47%), ask peers (17%), ask the teacher (7%), and are not relevant to KBM (4%). Student learning outcomes by applying the model of Group Investigation cycle I and II show individuals completed as many as 13 students and 29 students. Keywords : Model GI, Learning Activities, Learning Outcomes Abstrak : Upaya Peningkatan Aktivitas Belajar Melalui Model Kooperatif Tipe Group Investigation Mata Pelajaran Bahasa Indonesia Kelas VII-7 SMPN 1 Namorambe. Penelitian ini menerapkan model pembelajaran kooperatif tipe goup investigation. Dengan subjek penelitian adalah siswa kelas VII-7 SMP Negeri 1 Namorambe, berjumlah 33 siswa. Hasil penelitian;(a) aktivitas siswa menurut pengamatan Siklus I menulis dan membaca (45%), bekerja (24%), bertanya sesama teman (11%), bertanya kepada guru (7%), dan yang tidak relevan dengan KBM (14%). Aktivitas siswa pengamatan Siklus II menulis dan membaca (26%), bekerja (47%), bertanya sesama teman (17%), bertanya kepada guru (7%), dan tidak relevan dengan KBM (4%). (b) Hasil belajar siswa dengan menerapkan model Group Investigation siklus I dan II menunjukkan individu tuntas sebanyak 13 orang siswa dan 29 orang siswa.Kata kunci : Model GI, Aktivitas Belajar, Hasil Belajar